2020
DOI: 10.1080/0309877x.2020.1853687
|View full text |Cite
|
Sign up to set email alerts
|

A ‘new (ab)normal’?: Scrutinising the work-life balance of academics under lockdown

Abstract: In March 2020 virtually all UK universities were suddenly thrown into an unprecedented and sudden closure of campus and facilities owing to the British Government's Covid-19 pandemic lockdown policies. Further evidence suggests that this exacerbated existing gendered differences. This paper reports on UK academic responses from an international survey examining the work-life balance of academics under Covid-19 lockdown. The aim of the study was to examine the experiences and perceptions of academics, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…While some academic fathers in our study prioritized their role as a parent, this was a pre-pandemic decision and an uncommon one within higher education despite an argued shift towards more "equal" parenting roles (Gould & Lovato, 2019). Rather than radically shifting perceived roles, our findings suggest that preexisting gendered differences in work-life conflict (Colbeck & Drago, 2005;Fox et al, 2011;Wilton & Ross, 2017) were upheld amid the pandemic with academic mothers bearing a stronger work-life conflict burden (Ashencaen Crabtree et al, 2020).…”
Section: Perpetuation Of Gendered Work-life Conflict Patternsmentioning
confidence: 62%
See 1 more Smart Citation
“…While some academic fathers in our study prioritized their role as a parent, this was a pre-pandemic decision and an uncommon one within higher education despite an argued shift towards more "equal" parenting roles (Gould & Lovato, 2019). Rather than radically shifting perceived roles, our findings suggest that preexisting gendered differences in work-life conflict (Colbeck & Drago, 2005;Fox et al, 2011;Wilton & Ross, 2017) were upheld amid the pandemic with academic mothers bearing a stronger work-life conflict burden (Ashencaen Crabtree et al, 2020).…”
Section: Perpetuation Of Gendered Work-life Conflict Patternsmentioning
confidence: 62%
“…In academia, gender and the presence of young children at home were the most significant predictors of research disruptions (Myers et al, 2020). While some academics found that lockdowns and remote work created a quiet space and unhurried pace, which allowed for the "slowtime" required for creativity, writing, and scholarly production (Eriksen, 2001;Ylijoki & Mäntylä, 2003), academic mothers reported significant work-life challenges as they struggled to meet dual role expectations (Ashencaen Crabtree et al, 2020).…”
Section: Work-life Conflict Among Academic Mothers Amid the Pandemicmentioning
confidence: 99%
“…Greater strain on mental health. Over the weeks, leisure time and recreation spaces were restricted for parents and couples during the pandemic (Amri et al, 2020;Ashencaen Crabtree et al, 2021;Cheng et al, 2021;Hoffman, 2021;Israel et al, 2020;Lemos et al, 2020;Rawal, 2021;Rodríguez-Rivero et al, 2020;Shafer et al, 2020;Wong et al, 2021;Zamarro et al, 2021). Lack of personal and relaxation time, along with space limitations for intimate moments, can lead to stress, fatigue, anxiety, social isolation, and mental health problems (Carreri & Dornoni, 2020;Cheng et al, 2021;Goldberg et al, 2021;Hertz et al, 2021;Jain & Mohanan, 2020;Krisjane et al, 2020;Nikmah et al, 2020;.…”
Section: Asymmetrical Task Sharing and Maternal Overloadmentioning
confidence: 99%
“…For some parents, the experience of containment and integration of all life activities at home has resulted in less stress (Allen et al, 2021;Goldberg et al, 2021) as well as a more equal sharing of domestic tasks and childcare (Balenzano et al, 2020;Feng & Savani, 2020;Hjálmsdóttir & Bjarnadóttir, 2021;Lemos et al, 2020). Furthermore, for many people, the reduced commute time was an opportunity to improve their diet (prepare meals and eat at home), increase their physical activity, and reflect on their personal and professional life (Ashencaen Crabtree et al, 2021;Carreri & Dornoni, 2020;Craig & Churchill, 2020;Goldberg et al, 2021;Lemos et al, 2020;Schieman et al, 2021). According to Wong et al (2021), many parents would like to extend this work arrangement beyond pandemic.…”
Section: Facilitating Contextual Forcesmentioning
confidence: 99%
“…Notably, the COVID-19 pandemic changed our usual work patterns ( Ashencaen-Crabtree et al, 2021 ; Matulevicius et al, 2021 ; Möhring et al, 2021 ) suddenly forcing many science trainees to shift all of their work into their homes. While it remains uncertain how much the new patterns of making work arrangements more flexible (and therefore, less predictable) and shifting more work into workers’ homes will persist, it is important to recognize that even prior to the pandemic, both of these patterns were clearly causing problems with work-life balance and boundary marking ( Hayman, 2009 ; Felstead and Henseke, 2017 ).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%